Biologia reprodutiva e considerações sobre parasitismo em Lucina pectinata (Mollusca: Bivalvia) em um estuário tropical - Santana, Lígia Maria Borges Marques (2010)
In tropical estuaries, environments naturally complex due to the tides´s dynamics, the rainfall periods act as an intermediate disturbance. The environmental characteristics are important in the biota’s life history of the region, resulting in the establishment of reproduction patterns or interfering at organisms metabolism making them more susceptible to being affected by parasites. The bivalve Lucina pectinata (Gmelin, 1791), although appreciated in the Brazilian coast, was little studied in the country so far. This study aimed to characterize the reproductive biology of Lucina pectinata (Mollusca: Bivalvia, Lucinidae) from the Ceará river estuary, Fortaleza, CE, Brazil, and make considerations on trematode parasitism in this population, according to local environmental variations. Specimens collected had the gonads and gills assessed histologically. To determine the individuals sexual maturity, was employed gametogenic scale with four stages of gonadal development. Lucina pectinata presented continuous reproductive cycle, with peak spawning at dry season. The level of parasitism in the population was low, and the same is not being affected by the presence of parasites. Were observed proximity of the abiotic variables during the same season, distinguishing clearly the dry periods of rainy. Disturbance rainfall is discussed as a factor regulating the population of Lucina pectinata, contributing to its renewal and to control the incidence of trematode parasites.